The comparative analysis of the aggression level between women practicing Hip-Hop dancing and women practicing Brazilian Jiu-Jitsu - Pujszo, Małgorzata; Wyżlic, Paulina; Stępniak, Robert (Journal of Education, Health and Sport, 2018)
The comparison of aggression level between women practicing Hip-Hop and Brazilian Jiu-Jitsu against the average aggression level of Polish women. 27 women practicing Hip-Hop and 33 women practicing Brazilian Jiu-Jitsu were questioned using the Polish adaptation of the survey “Aggression questionnaire” by Buss, Perry from “Amity Institute” to check the aggression level. Gathered data was compared against the results of Polish women control group.